CLT PLAY AN IMPORTANT ROLE TO LEARN LANGUAGE EFFECTIVELY - Khalilova Olima Akhatovna (Scholar Express Journals, 2023)
As the language is taught for the functional purpose, a variety of linguistic forms are presented together. Students have to learn language properties i.e. cohesion and coherence which are helpful to combine sentences together. It is essential for them as they work with language at the discourse or super sentential (above sentence) level. In CLT, games, role plays, group work, pair work, etc. play an important role as they have certain feature in common to learn language effectively
Keywords: Cohesion; Coherence; Helpful; Approach